Results of surgical treatment of bone cysts in children - Levitsky, Anatoly; Golovatyuk, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The results of application of a treatment method algorithm for bone cysts in children on the basis of evaluation of treatment results in 62 patients with anevrismal and solitary bone cyst are presented. The stage of cyst course was determined on the basis of radiological examination and diagnostic puncture. At the stage of osteolysis one should use the drug-puncture treatment. Surgical intervention is indicated in case of failure of the drug-puncture treatment or after the cyst has entered the stage of circumscription. The method of resection and implant material are chosen on the basis of detection of the stage in the course of the cyst, its location and volume.